Polymorphisms of APOE and APOB genes and dyslipidemias in a South Brazilian Cohort - Cardozo Gasparin, Caroline; Viater Tureck, Luciane; Pereira Ferrari, Lilian; Lehtonen Rodrigues de Souza, Ricardo; Furtado Alle, Lupe (Brazilian Journal of Implantology and Health Sciences, 2024)
Dyslipidemias are closely associated to the development of cardiovascular and cerebrovascular diseases, and therefore of great importance in public health. Many genes influence lipid levels, such as APOE and APOB. The present study aimed to investigate the effects of APOE gene alleles (rs7412: C>T and rs429358: T>C), and R3500Q mutation of APOB gene (rs5742904: G>A) in lipid levels in a South Brazilian cohort. 214 individuals were analyzed and the frequencies of APOE ε2, ε3 and ε4 alleles were found respectively as 9.25 ± 0.4625; 70.5 ± 3.525 and 20.25%± 1.401, while the frequency of R3500Q mutation of the APOB gene was 4.46 ± 1.00%. The ε4 allele was significantly more frequent in subjects with higher TC (Total Cholesterol) and LDL-C levels, while significantly higher frequency of the ε2 allele was found in individuals with higher HDL-C levels. The R3500Q mutation was suggested as a risk factor for higher TC levels, regardless gender and age (β = 21.326 ± 10377.78, p = 0.001).